Increasing Students' Motivation in Learning English through Song at Elementary School - Hidayat, Ika Nuriyanti (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2024)
The aim of this research is to increase the motivation of elementary school students at SDN Dau Jetis Malang. At this school, English is one of the subjects that students don't like because it is difficult to understand every vocabulary spoken by the teacher. This school was also used as a research object because the location of this school is quite accessible from the city. The reason for the lack of knowledge regarding vocabulary in English is understandable because elementary school students still do not realize the benefits of studying a foreign language such as English. Here researchers increase students' motivation in learning English by using songs. Songs are known to have great power to attract attention and increase student activity in class. This is proven by the extraordinary activities in the English class. The songs given are children's songs that students often hear so that students understand the melody they hear. The researcher gave 3 songs such as five little ducks for counting songs, twinkle-twinkle little stars for calm songs and ABC song for pronouncing the alphabet. These three songs have been proven to increase students' motivation at SDN Dau Jetis Malang in learning English. the class becomes livelier and more colorful. Increasing students' motivation to use songs to learn English has proven successful for elementary school students and it is hoped that English teachers can improve their ability to use English songs for children.